(untitled) (Forum Penelitian Agro Ekonomi, 2016)
Meat Self-Sufficiency Program (PSDS) since 2000 has been launched three times. This paper aims to assess implementation, achievement, constraints and problems of National PSDS as well as the solution proposed. The study shows that meat self-sufficiency achievement is dynamic and in general there are some improvement on concept, policy instrument, and program management of PSDS 2014. Nevertheless, many constraints are found from upstream to downstream including bad management of cows’ distribution and import. All of these constraints lead to unrealized target of meat self-sufficiency in 2014. Cows and their derivative products import are still required to sustain cows’ population growth in Indonesia and to stabilize domestic meat price. In order to accelerate the achievement of the target, besides production aspect improvement, distribution system of cows and meat including its infrastructure also needs perfection. Another important issue is data accuracy on domestic supply and demand such that the government can estimate accurate required volume of meat import. Administration, bureaucracy and transparency enhancement on meat import implementation are urgent to avoid disorder of cows, meat and its derivative products import. Support from related institutions is needed for the achievement of national meat self-sufficiency.